TRACER STUDY OF MANAGEMENT DEPARTMENT, GANESHA UNIVERSITY OF EDUCATION YEAR 2013 - 2015 - Komang Krisna Heryanda (Universitas Pendidikan Ganesha, 2018)
Tracer study is an approach that allows college institutions to obtain information about possible deficiencies in the educational process and learning process. It can also be the basis for future improvement planning activities. This tracer study research could see the illustration of two sides, namely the graduates’ side as the service user of the education institution and the stakeholder side as the graduate user. This tracer study aimed at getting an overview of the lecture program that had been obtained by the graduates, as well as the quality of graduates produced by the Department of Management. The target of this tracer study was the alumni of Management Department graduates in 2013 - 2015 and the stakeholders in this case were the service users of Management department graduates. The results of this study indicated that the graduates produced by the Management Department had an average waiting time of less than 12 months (1 year) to obtain a job. The types of jobs graduated from Management Department were mostly in the private sector, there was only one person who decided to become an entrepreneur. Most of the graduates earned 1 million rupiah - 3 million rupiah per month as the first income. Most graduates were satisfied with the aspects of learning gained during their study in Management Departments as well as the response about learning experience. Graduates were quite satisfied with the learning experience during the course in Management Department. The graduates complained about inadequate lecture facilities condition. It was certainly a serious significance to be addressed immediately. Most of the users of the graduates (stakeholders) were satisfied with the ability of management department graduates. It was just the aspect of English language skills that were still considered less. In accordance with English language skills, communication skills were also complained by graduate users (stakeholders). Keywords: Alumni of Management, Tracer StudyTracer study is an approach that allows college institutions to obtain information about possible deficiencies in the educational process and learning process. It can also be the basis for future improvement planning activities. This tracer study research could see the illustration of two sides, namely the graduates’ side as the service user of the education institution and the stakeholder side as the graduate user. This tracer study aimed at getting an overview of the lecture program that had been obtained by the graduates, as well as the quality of graduates produced by the Department of Management. The target of this tracer study was the alumni of Management Department graduates in 2013 - 2015 and the stakeholders in this case were the service users of Management department graduates. The results of this study indicated that the graduates produced by the Management Department had an average waiting time of less than 12 months (1 year) to obtain a job. The types of jobs graduated from Management Department were mostly in the private sector, there was only one person who decided to become an entrepreneur. Most of the graduates earned 1 million rupiah - 3 million rupiah per month as the first income. Most graduates were satisfied with the aspects of learning gained during their study in Management Departments as well as the response about learning experience. Graduates were quite satisfied with the learning experience during the course in Management Department. The graduates complained about inadequate lecture facilities condition. It was certainly a serious significance to be addressed immediately. Most of the users of the graduates (stakeholders) were satisfied with the ability of management department graduates. It was just the aspect of English language skills that were still considered less. In accordance with English language skills, communication skills were also complained by graduate users (stakeholders).